GOVERNMENT RESPONSIBILITY FOR PERSONAL DATA ON THE SATUSEHAT APPLICATION IN INDONESIA - Wau, Hilbertus Sumplisius M.; Aspan, Henry; Sumarno, Sumarno (NOMOI Law Review, 2025)
The COVID-19 pandemic in Indonesia represents a crisis that demands swift and effective management. The government is required to take a leading role in breaking the chain of virus transmission. One of the strategies undertaken was the utilization of the SATUSEHAT application. However, the use of this application carries potential risks of personal data breaches, as users are required to submit personal information as a condition for access. Therefore, it is important to conduct a study on the government’s responsibility in safeguarding citizens’ personal data following the implementation of the SATUSEHAT application. This research employs a normative legal method supported by empirical data, using a descriptive-analytical approach, and is grounded in both statutory and case-based legal frameworks. The study relies on secondary data as legal materials, including primary, secondary, and tertiary legal sources, collected through literature study and documentary analysis. The analysis adopts a qualitative research approach to draw final conclusions. This study finds that the government’s responsibility for personal data in the SATUSEHAT application includes the obligation to ensure protection by implementing robust data security systems and conducting data protection impact assessments for each data subject. Moreover, the government is also obliged to terminate the processing of personal data once the intended purpose has been achieved, accompanied by the deletion and destruction of such data. This measure aims to minimize the risk of personal data breaches committed by unauthorized third parties (hackers).